The Effect Of The Efficiency Of Murabaha Financing On The Financial Performance Of Islamic Banks (Applied Study On Private Islamic Banks In Syria) - المملوك انس (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to demonstrate the efficiency of murabaha financing on the financial performance and risks of Islamic banks operating in Syria during the period (2009-2018) and to demonstrate the great and effective role of the murabahah formula in Islamic banking finance. The study sample included the Sham Bank, the Syria International Islamic Bank, and Al Baraka Bank - Syria, where data were collected from the reality of the annual financial reports and the financial data issued by the banks, the study sample. In order to achieve the objectives and reach the results, the study relied on the analytical and descriptive approach and carried out simple and multiple linear regression analysis to test the hypotheses of the study and answer the study questions. One of the most important findings of the study is the presence of a statistically significant effect of the efficiency of murabaha financing on the return on assets in Islamic banks operating in Syria, as it is a good indicator of the increase in demand for murabaha financing, which increases the volume of investments and assets of the bank and thus is reflected in the returns achieved in The future The study also found a statistically significant impact of murabaha financing on the return on property rights in Islamic banks operating in Syria. his means that the bank has the ability to make good use of its assets, while the efficiency of murabahah financing does not have a significant impact on the financial performance in Islamic banks operating in Syria. This is due to the fact that efficient grant policies regarding murabaha financing directly affect the increase Bank profits, and on the bank’s financing policies. The most important thing recommended by the study is the need for bank management to pay more attention to efficient grant policies and procedures in relation to murabaha financing because of their impact on the bank’s profitability and its ability to remain in the banking market.